The feelings of guilt and shame in alcohol dependent patients - Kalyoncu, Ö. Ayhan; Mırsal, Hasan; Pektaş, Özkan; Gümüş, Ömer; Tan, Devran; Beyazyürek, Mansur (Journal of Dependence, 2002)
Objective: It was proposed that feelings of guilt and shame play important role in alcohol-dependence.The purpose of this study was to determine the feelings of guilt and shame in alcohol dependent patients in remission.Method: One Hundred-two alcohol dependent patients who met the DSM-IV criteria for alcohol dependency, hospitalized and treated previously for alcohol dependency, and was in remission for at least six months were studied. The control group included 72 people who were age and sex correlated with the study group and had no psychiatric diagnoses or treatment at all. Having the treatment protocol in our clinic by hospitalization previously, the lack of the other psychiatric disorder, the lack of psyhotrophic drug use for the past one month, and no alcohol use for the past six months were the including criteria. Sociodemographic Data Form, Guilt and Shame Scale, Rotter’s Internal-External Control Scale, Hamilton Depression Rating Scale were used in this study.Results: It was found that there wasn’t any difference in sociodemographic characteristics between the study group and the control group. In the other hand, it was found that there were significant differences in the scores of Guilt and Shame Scale (t=25,6 p=,0), Rotter’s Internal-External Control Scale(t=7,3 p=,0), Hamilton Depression Rating Scale (t=11,5 p=,0) between two groups statistically.Conclusion: Although alcohol dependent patients were in remission for at least six months, alcohol dependent patients had the feelings of guilt and shame more intense than the conrol group. This suggests that further studies are needed to understand the effect of this result on the remission period by considering sociodemographic clinical characteristics.
Keywords: Alcohol dependence; guilt; shame